Homem e/ou mulher: as representações do masculino e feminino em imagens de moda - Queiroz, Mário Antônio Pinto de (2013)
The purpose of this research is to identify how fashion image represents gender in examples drawn out from fashion magazines and from advertising campaigns in Brazil, France, England and United States in the beginning of the 21st Century. We seek to understand how female and male roles have been differently interpreted and what they may signal within the transformations occurred in the plural and inter civilizatory societies. We started from concepts of images as collective symbolizations in Belting; from understanding photography as image of concepts , as in Flusser; and from its distinction in Barthes. Kamper s concepts of corporeal dimensions and imaginary is also included in addition to seeking in Aganbem the understanding of contemporaneity . Researches of photography production in fashion, based on the ideas of designers and editors, such as Rebecca Arnold, also contribute with this research. The master s dissertation, O herói desmascarado an imagem do homem na moda (The unmasked hero male image in fashion) appears as a starting point. The results showing how male gender has been represented in fashion photography have opened up a broader discussion on how different genders are treated in contemporary society. We want to understand what would mean a female and male identity crisis crisis understood as in Morin in a scenario in which images point out variations and share space with other severe and stereotyped standards. We have followed the paths travelled by fashion and by photography from their beginning into the 80 s and 90 s up into the 21st century. We want to understand how the discourse of diversity - identified in bodies and in the social-cultural- political roles challenges the standards, how ruptures are generated and what they may mean in the transformation of individuals and of the community